THE PREVALENCE OF DENTAL ANOMALIES IN A TURKISH POPULATION - Gamze Aren; Yeliz Güven; Ceren Güney Tolgay; İlknur Özcan; Özlem Filiz Bayar; Taha Emre Köse; Gülhan Koyuncuoğlu; Gülsüm Ak (Istanbul University, 2015)
Purpose: The aim of the present study was to investigate the prevalence of dental anomalies in a Turkish population according to the gender and age. Materials and Methods: A retrospective study was performed using panoramic radiographs of 2025 patients (885 males and 1140 females) ranging in age from 9 to 35 (mean age 25.61±10.04) years attending Department of Oral Radiology, University of Istanbul, Faculty of Dentistry. These patients were examined to determine the presence of developmental dental anomalies involving hypodontia, hyperdontia, microdontia, taurodontism and other root anomalies. The incidence of these anomalies were assessed according to the gender and age. Results: Among the 2025 subjects, a total of 96 individuals (42 males and 54 females) showed at least one of the selected dental anomalies (4.74%). Tooth agenesis was the most common dental abnormality (1.77%) followed by taurodontism (1.18%), hyperdontia (0.79%), microdontia (0.54%) and root anomalies (0.44%), respectively. Conclusion: Tooth agenesis is the most common developmental dental anomaly in the studied Turkish population followed by taurodontism.